Measuring Dietary Restraint Status: Comparisons between the Dietary Intent Scale and the Restraint Scale - Boyce, Jessica A.; Gleaves, David H.; Kuijer, Roeline G. (Frontiers in Nutrition, 2015)
The measurement of young women’s self-reported dietary restraint status is complex. Compared to Herman and Polivy’s commonly utilized Restraint Scale (RS), Stice’s Dietary Intent Scale (DIS) is less understood. Because the DIS is becoming a popular research tool, it is important to understand how this scale compares to more traditional measures of restraint. We conducted two correlational studies (Study 1 N = 110; Study 2 N = 216) to ascertain the similarities and the differences between the DIS and – as a comparison measure – the well-researched RS. We explored how the two scales were related to several body image variables (e.g., thin-ideal internalization); with a range of self-regulatory variables (e.g., dispositional self-control); with observed food intake during a taste test; and with 18-month weight change (Study 2 only). Participants were female University students and were not selected for dieting or disordered eating. Unlike RS scores, DIS scores were not significantly correlated with the majority of variables tapping into unsuccessful self-regulation. However, our data also highlighted similarities between the two restraint scales (e.g., association with 18-month weight-loss) and demonstrated that not only were participants’ DIS scores un-related to unsuccessful self-regulatory variables, neither were they related to the variables tapping into successful self-regulation.